Rhetorical Connections in the Grammarians’ Preference for Sibawayh’s View - Hassan Khudair Al-Shawi, Assist. Lect . Ahmad; Abdul Kazem , Prof. Dr. Mohammed (Basra studies journal, 2025)
Discourse has been of great significance since ancient times, serving as the primary means by which individuals connect with their social environment. As a result, its forms and purposes are diverse, encompassing religious, political, philosophical, promotional, and more. Regardless of the variety of its types, the speaker’s primary goal is often to make their discourse more impactful and persuasive to the audience. To achieve this, the speaker employs various persuasive techniques, including dialogue, skillful structuring, presenting supporting arguments, and other rhetorical strategies. One prominent theory that addresses persuasive discourse is the theory of linguistic argumentation by Ducrot and Anscomber. Of particular interest in their theory are the rhetorical links that play a key role in the argumentative process.